2018
DOI: 10.1111/jgs.15182
|View full text |Cite
|
Sign up to set email alerts
|

Personality Changes During the Transition from Cognitive Health to Mild Cognitive Impairment

Abstract: BACKGROUND/OBJECTIVES: Behavioral problems in individuals with Alzheimer's disease (AD) impose major management challenges. Current prevention strategies are anchored to cognitive outcomes, but behavioral outcomes may provide another, clinically relevant opportunity for preemptive therapy. We sought to determine whether personality changes that predispose to behavioral disorders arise during the transition from preclinical AD to mild cognitive impairment (MCI). DESIGN: Longitudinal observational cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 51 publications
2
38
0
3
Order By: Relevance
“…It is likely that these participants were less apathetic, with intact initiative or motivation to complete the study. Although participants with dementia were excluded from the analysis, some individuals were characterized by cognitive impairment that may be associated with their self‐report of personality traits . Our sensitivity analyses indicated that the associations were similar when participants with mild cognitive impairments were excluded from the analyses.…”
Section: Discussionmentioning
confidence: 89%
“…It is likely that these participants were less apathetic, with intact initiative or motivation to complete the study. Although participants with dementia were excluded from the analysis, some individuals were characterized by cognitive impairment that may be associated with their self‐report of personality traits . Our sensitivity analyses indicated that the associations were similar when participants with mild cognitive impairments were excluded from the analyses.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the reported link between an individual's own cognitive concerns (rather than those of an informant) and AD biomarkers in asymptomatic individuals suggests that there may be additive utility in examining trajectories of cognitive complaints alongside cognitive decline to predict risk for clinical progression . This may also be extended to measures of mild neurobehavioral changes as well as potentially novel measures of health outcomes developed in coordination with patient and caregivers to better identify what is of value from an individual's perspective (e.g., driving, perceived competence, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reported link between an individual's own cognitive concerns (rather than those of an informant) and AD biomarkers in asymptomatic individuals 26 suggests that there may be additive utility in examining trajectories of cognitive complaints alongside cognitive decline to predict risk for clinical progression. 27 This may also be extended to measures of mild neurobehavioral changes [28][29][30]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding depression, for which we found three of four tests declining more rapidly in MCI converters relative to nonconverters postinflection, we have previously shown in a normal aging cohort that there was no differential acceleration in depression scores among e4 carriers . During the transition from normal aging to MCI, however, there is a change in personality and behavioral measures, including depression scores . This temporal pattern suggests that depression, rather than being a risk factor, is more likely an early manifestation of neurodegeneration.…”
Section: Discussionmentioning
confidence: 49%
“…39 During the transition from normal aging to MCI, however, there is a change in personality and behavioral measures, including depression scores. 40 This temporal pattern suggests that depression, rather than being a risk factor, is more likely an early manifestation of neurodegeneration. Further observation will be needed to confirm whether these subclinical changes during the pre-MCI stage are predictive of subsequent behavioral disorders.…”
Section: F I G U R Ementioning
confidence: 99%